(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the role of innovative software educational tools in the formation and development of methodological competence of future biology teachers, their capabilities, advantages and effectiveness. It also highlights the role of modern web platforms and interactive resources in the educational process.